Articulating five liquids: a single speaker ultrasound study of Malayalam - James M Scobbie; Reenu Punnoose and Ghada Khattab
We investigate the lingual shapes of the five liquid phonemes of Malayalam: two rhotics, two laterals and a more problematic 5 th liquid. Ultrasound is used to image the mid-sagittal tongue surface, mainly in an intervocalic within-word /a__a/ context. The dark retroflex lateral and trill have a retracted tongue root and lowered tongue dorsum, while the three other clear liquids show advanced tongue root and dorsal raising. The 5 th liquid is post- alveolar and laminal. Some additional data from an /a__i/ context is considered: the liquids are slightly clearer before /i/: all have a slightly advanced tongue root, and all bar the trill show palatalization. Dynamically, the trill and retroflex lateral have a very stable tongue root in /a__a/, and the 5 th liquid has unusual anterior kinematic properties which require further investigation.